A Fast Localization of Multiple Harmonic Sources for Rectifier Loads by Utilizing Periodogram - M. Hatta Jopri; A. Rahim Abdullah; Mustafa Manap; M. Rahimi Yusoff; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper introduces a fast method to localize the multiple harmonic sources (MHS) for rectifier based loads in power distribution system by utilizing periodogram technique with a single-point measurement approach at the point of common coupling (PCC). The periodogram is a fast and accurate technique for analyzing and distinguishing MHS location in power system. Matlab simulation is carried out several unique cases on IEEE test feeder cases due to validate the proposed method. The identification of MHS location is based on the significant relationship of spectral impedance which are fundamental impedance (Z1) and harmonic impedance (Zh) that's extracted from an impedance power spectrum. It is verified that the proposed method is fast, accurate, and cost efficient in localizing MHS. In addition, this method also contributes 100% correct identification of MHS location.